Social EEG: A novel neurodevelopmental approach to studying brain‐behavior links and brain‐to‐brain synchrony during naturalistic toddler–parent interactions. Issue 3 (20th March 2022) - Norton, Elizabeth S.; Manning, Brittany L.; Harriott, Emily M.; Nikolaeva, Julia I.; Nyabingi, Olufemi Shakuur; Fredian, Kaitlyn M.; Page, Jessica M.; McWeeny, Sean; Krogh‐Jespersen, Sheila; MacNeill, Leigha A.; Roberts, Megan Y.; Wakschlag, Lauren S.
Abstract: Despite increasing emphasis on emergent brain‐behavior patterns supporting language, cognitive, and socioemotional development in toddlerhood, methodologic challenges impede their characterization. Toddlers are notoriously difficult to engage in brain research, leaving a developmental window in which neural processes are understudied. Further, electroencephalography (EEG) and event‐related potential paradigms at this age typically employ structured, experimental tasks that rarely reflect formative naturalistic interactions with caregivers. Here, we introduce and provide proof of concept for a new "Social EEG" paradigm, in which parent–toddler dyads interact naturally during EEG recording. Parents and toddlers sit at a table together and engage in different activities, such as book sharing or watching a movie. EEG is time locked to the video recording of their interaction. Offline, behavioral data are microcoded with mutually exclusive engagement state codes. From 216 sessions to date with 2‐ and 3‐year‐old toddlers and their parents, 72% of dyads successfully completed the full Social EEG paradigm, suggesting that it is possible to collect dual EEG from parents and toddlers during naturalistic interactions. In addition to providing naturalistic information about child neural development within the caregiving context, this paradigm holds promise for examination of emerging constructs such as brain‐to‐brain synchrony in parents and children.